Enhancing Deep Learning Facilitator Competence through Blended Training: An Action Research Insight from Hinterland Area of Indonesia - Pohan, Albert Efendi; Sibarani, Hos Arie Ramadhan; Nasution, Laskar Muda; Siregar, Ajizah; Osriza Betri; Hure, Frudensia Mawar; Bherti Angelia; Netti; Marwati; Sfarizal (Jurnal Akuntabilitas Manajemen Pendidikan, 2026)
Teacher competence is the primary determinant of the successful implementation of Deep Learning in Indonesia as a national policy to enhance educational quality in pursuit of Indonesia Emas 2045. Therefore, improving teacher competence through effective, efficient, and sustainable technology-assisted training must become a top government priority. Based on this fundamental urgency, this study was conducted to enhance the competence of Deep Learning facilitators through blended-based training in hinterland regions of Riau Islands Province, Indonesia. In line with this objective, the research employed an Action Research design consisting of two cycles through the stages of planning, action, observation, and reflection. The study involved 3,140 teachers for the preliminary research, 25 participants for the pilot study, and 37 trainees from hinterland areas in Riau Islands Province, Indonesia. The findings indicate that blended-based training can improve Deep Learning facilitator competence, including competence in designing lesson plans, peer teaching, and understanding Deep Learning concepts contextualized to hinterland regions. This study provides a theoretical contribution that blended-based training is relevant for improving teacher competence in Indonesia’s hinterland areas. The results offer new directions for future research by optimizing blended-based training to enhance teachers’ competence in implementing Deep Learning adaptively according to the hinterland context.